Estimating pediatric asthma prevalence in rural senegal: A cross‐sectional survey. Issue 3 (23rd August 2016) - Hooper, Laura G.; Dieye, Yakou; Ndiaye, Assane; Diallo, Aldiouma; Fan, Vincent S.; Neuzil, Kathleen M.; Ortiz, Justin R.
Summary: Rationale: In Senegal, the prevalence of childhood asthma and utilization of appropriate asthma therapies is unknown. Methodology: We used the International Study of Asthma and Allergies in Childhood (ISAAC) survey instrument to assess childhood respiratory health in rural Senegal. We interviewed the caregivers of children aged 5 through 8 years of age in the four largest Niakhar villages in August 2012. Results: We interviewed 1, 103 primary caregivers for 1, 513 children, representing 91% of all age‐eligible children in the study area. Overall, 206 (14%) children had wheeze at any time in the past, 130 (9%) had wheeze within the past year, and only 41 (3%) reported a clinical diagnosis of asthma. Among children with wheeze within the past year, 81 (62%) had symptoms of severe asthma. Nocturnal cough was reported in 186 (14%) children who denied any history of wheezing illness. Only four (3%) children with wheeze in the past year had ever received bronchodilator therapy. Children with wheeze in the past year were significantly more likely to seek medical care for respiratory symptoms and to be perceived as less healthy than their peers. Children of lower socioeconomic status were significantly more likely to have wheeze. Conclusions: Nearly one in ten children in Niakhar, Senegal had symptoms suggestive of asthma; however, few children have a diagnosis of asthma or use appropriate therapies. This study highlights an opportunity to raise community awareness of asthma in rural Senegal and to increase access to appropriate medical therapies.Pediatr Pulmonol. 2017;52:303–309. © 2016 Wiley Periodicals, Inc.